DETEKSI DINI KANKER LEHER RAHIM MELALUI TES IVA DI PUSKESMAS JATEN II KABUPATEN KARANGANYAR - Ropitasari Ropitasari (LPPM UNS, 2014)
The Community Health Center Jaten II was located in Ngringo Village, Karanganyar, the solidest village in Karanganyar. Amount of W/PUS are 5396 while just 364 of them have been screened by IVA test during 20 months. This result is similar with 8,43% from the Puskesmas’s target that is 4316 W/PUS (80% of totally W/PUS). So most required the breakthrough to solve this problem with follow-up Early Detection of Cervix Uteri Cancer by IVA Test. Early detecting, giving information about Cancer of Cervix Uteri, and motivating for the inspection of routine periodically to health facility. Patient screening with the Communication, Information and Education at PKK meeting, Posyandu cadre, inter sectoral. The population is Woman / Fertile Age Couple ( W/PUS). Among 102 participants, there are 4 mothers with positive of precancer lesion, one a mother who was recovered and other has cancelled to follow because pregnant. Conclusion that after conducted by counselling and inspection of IVA test, there are improving of mother knowledge regarding early detection of cervix uteri cancer by inspection of IVA Test. Suggestion. Women who has active sexual should to IVA test. Once a year for men and adult society has been sexual active should support and motivate their women to intend IVA Test examination. To Community Health Center in order to increase of DDKLR.